Роль фінансового фактора у забезпеченні сталого розвитку територіальних економічних систем - Тичковська, Л.П. (Економіка природокористування і охорони довкілля, 2013)
Стаття присвячена розробці теоретико-методологічних засад управління сталим розвитком ТЕС на основі відтворювального підходу. Розкриває об’єктивні передумови відтворення територіальних економічних систем у національній економіці. The article is devoted to theoretical and methodological bases of managing sustainable development of TES on the basis of a reproduction approach elaboration. In article it is opened objective bases of territorial economic systems reproduction in national economy are exposed. Scientific bases of the financial provision mechanism and sustainability management of TES are grounded. The analysis of functioning of territorial economic systems of Ukraine is performed, tendencies of their financial provision are revealed. Conceptual bases of management of national economy sustainable development through territorial reproduction processes are exposed, financial mechanism of sustainable development management and its institutional support are grounded. The scheme of project financing of territorial economic systems sustainable development and attraction of territorial natural resources in sustainable projects is proposed.